Spatial patterns of immunogenetic and neutral variation underscore the conservation value of small, isolated American badger populations. (21st August 2016) - Rico, Yessica; Ethier, Danielle M.; Davy, Christina M.; Sayers, Josh; Weir, Richard D.; Swanson, Bradley J.; Nocera, Joseph J.; Kyle, Christopher J.
Abstract: Small and isolated populations often exhibit low genetic diversity due to drift and inbreeding, but may simultaneously harbour adaptive variation. We investigate spatial distributions of immunogenetic variation in American badger subspecies ( Taxidea taxus ), as a proxy for evaluating their evolutionary potential across the northern extent of the species' range. We compared genetic structure of 20 microsatellites and the major histocompatibility complex (MHC DRB exon 2) to evaluate whether small, isolated populations show low adaptive polymorphism relative to large and well‐connected populations. Our results suggest that gene flow plays a prominent role in shaping MHC polymorphism across large spatial scales, while the interplay between gene flow and selection was stronger towards the northern peripheries. The similarity of MHC alleles within subspecies relative to their neutral genetic differentiation suggests that adaptive divergence among subspecies can be maintained despite ongoing gene flow along subspecies boundaries. Neutral genetic diversity was low in small relative to large populations, but MHC diversity within individuals was high in small populations. Despite reduced neutral genetic variation, small and isolated populations harbour functional variation that likely contribute to the species evolutionary potential at the northern range. Our findings suggest that conservation approaches should focus on managing adaptive variation across the species range rather than protecting subspecies per se.